Tensile Strength of the Eggshell Membranes - Jana Strnková (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
The mechanical behaviour of eggshell membranes under tensile loading has been studied. Samples from different bird species (hen, goose and Japanese quail) have been used. Samples were cut out of the membrane in latitudinal direction. TIRAtest 27025 tensile testing machine equipped with a 200 N load-cell was used. Tensile deformation exhibits both non-linear as well as linear region. The experiments were performed at five loading velocities 1, 10, 100, 400 and 800 mm.min−1. The main parameters describing the eggshell strength increase with the loading rate. This dependence exhibits the same qualitative features as the rate dependence of the eggshell strength.